Effect of Discharge Plan on Outcomes of Patients with Lumbar Disc Herniation Surgery - Mabrouka A. Abd- Ella; Tahany A. Elsenousy; Dalia A. Abdelatief; Samar F. Marzouk (Evidence-Based Nursing Research)
Context: Discharge planning for patients undergoing lumbar disc herniation surgery is considered a strategy for promoting their home and community outcomes.